Diseño y simulación de la red externa de agua potable para el barrio Togueros, parroquia San Pedro de la Bendita, cantón Catamayo, provincia de Loja - Maldonado Machuca., Steve Efraín (2022)
The design of external drinking water networks-REDAP for rural populations is essential for the rational provision of water in sectors where storage and subsequent treatment are limited. This project focuses on the design and simulation of an external drinking water network -REDAP for the Togueros sector, San Pedro de la Bendita parish, where the demand for flow of the users of the Togueros sector was characterized by two methods or regulations. The INEN 5 regulation established by SSA (Undersecretariat of Environmental Sanitation), describes a methodology based on the daily allowance per inhabitants in rural sectors or less than 1000 inhabitants applied to REDAP, while the second NEC-11 regulation leans on a methodology by instantaneous flow of the sanitary devices arranged in a typical dwelling, that is, in its RIDAP (internal drinking water network). The AutoCAD software was used to locate the points of demand of the users and graph the trajectory of the network, together satellite images were taken from the Google Earth Pro software where the elevation of these points was identified. Likewise, with the intervention of the EpaCAD software, REDAP was transported to the Epanet program, where the drinking water networks were simulated and analyzed. Obtaining the adequate diameters of the pipes according to the regulation of the NEC-11 Regulation, which proposes supply pressures for homes in the range of 15 to 50 mwc, while the velocity in the pipes is between 0.6 and 2.5 m / s. The results show that the H and I2 branches have low speeds, which led to the implementation of a pumping system in the RIDAP of the houses of these branches. Keywords: drinking water, pump, Epanet, Google Earth Pro, REDAP, hydraulic networks, RIDAP, rural areas.